2000
DOI: 10.1046/j.1365-2265.2000.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and pathogenesis of thyrotoxicosis in adult Melanesians in Papua New Guinea

Abstract: The cause of this apparent sudden increase in Graves' disease in the coastal region around Port Moresby, an apparently iodine-replete area, remains unexplained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…However, many papers on thyroid disease report the results from pathology specimens and, in the absence of an endocrine clinic, the data are unreliable as most cases of thyrotoxicosis are treated medically, not surgically. Recently a high prevalence of autoimmune thyroid disease (Graves’ and Hashimoto’s) has been reported from Papua New Guinea 59 . In SE Asia juvenile Graves’ disease has been reported from Hong Kong 60 where adult Graves’ disease is also common 61 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many papers on thyroid disease report the results from pathology specimens and, in the absence of an endocrine clinic, the data are unreliable as most cases of thyrotoxicosis are treated medically, not surgically. Recently a high prevalence of autoimmune thyroid disease (Graves’ and Hashimoto’s) has been reported from Papua New Guinea 59 . In SE Asia juvenile Graves’ disease has been reported from Hong Kong 60 where adult Graves’ disease is also common 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently a high prevalence of autoimmune thyroid disease (Graves' and Hashimoto's) has been reported from Papua New Guinea. 59 In SE Asia juvenile Graves' disease has been reported from Hong Kong 60 where adult Graves' disease is also common. 61 Thyrotoxicosis affects 1.58% of the population in Singapore.…”
Section: Pathologymentioning
confidence: 99%
“…Iodoamino acids such as monoiodotyrosine (MIT), diiodotyrosine (DIT), triiodothyronine (T3) and thyroxine (T4) have been identifi ed in S. thunbergii (Ito et al ., 1976). T3 and T4 are the same hormones produced by the thyroid gland central to metabolic regulation, and have a signifi cant role in Grave's disease and Hashimoto's thyroiditis (Michelangeli et al ., 2000). It is possible that some compounds mediating the iodoamino acids in Sargassum may affect human thyroid metabolism, and contribute to a traditionally observed pharmacological effects in thyroid disease (Liu et al .…”
Section: Brown Macroalgaementioning
confidence: 99%
“…nodular goiter as the main biological basis of IIH was relatively rare in this area before USI. In addition, the significant increased incidence of hyperthyroidism found in Panshan with borderline iodine deficiency but without the influence of USI, suggested that the increment in iodine intake is not the only cause leading to an increase of hyperthyroidism (15,16).…”
Section: Panshanmentioning
confidence: 99%